PENGARUH MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT (CMP) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Sri Rahmawati Fitriatien; Ibut Priono Leksono; Prayogo Prayogo (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2021)
The research was conducted in students’ mathematical problem - solving skills and there are many students who have difficulty learning mathematics. This is due to the teacher - centered learning. Efforts that can be made to the learning process in the classroom can improve students ' problem - solving skills by selecting and using the relevant learning model. One such relevant learning model is the Connected Mathematics Project (CMP) learning model. The research problem was formulized in "is there any influence of the Connected Mathematics Project (CMP) learning model to the mathematical problem - solving skills of SMP students?". This research aims to determine the influence of CMP learning model to the mathematical problem solving skills of grade VIII SMPN 12 Surabaya. The research method was plied in quantitative methods. Research samples were acquired by two classes with random sampling techniques consisting of experimental classes and control classes, each as much as 37 students. Analysis of the data used in this study is test-T. The results of the study using the test-T showed that there was a influence of the CMP learning model of students learning outcomes of class VIII SMP Negeri 12 Surabaya year 2019/2020 of The System Material of Two-Variable Linear Equations (SPLDV). In addition, students’ mathematical problem solving capabilities include understanding the problems in the experiment class higher than the control class.